2016
DOI: 10.1155/2016/9012605
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oil of Ocimum basilicum L. and (−)‐Linalool Blocks the Excitability of Rat Sciatic Nerve

Abstract: The racemate linalool and its levogyrus enantiomer [(−)-LIN] are present in many essential oils and possess several pharmacological activities, such as antinociceptive and anti-inflammatory. In this work, the effects of essential oil obtained from the cultivation of the Ocimum basilicum L. (EOOb) derived from Germplasm Bank rich in (−)-LIN content in the excitability of peripheral nervous system were studied. We used rat sciatic nerve to investigate the EOOb and (−)-LIN effects on neuron excitability and the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Basil and its essential oil are often used in traditional medicine (Irondi et al 2016;Ezeani et al 2017;Bae et al 2020), cosmetics (Vivas Castaño et al 2016;Volpe et al 2018;Yeşil et al 2020), and pharmacology (Sestili et al 2018;Zhan et al 2020). Among the pharmacologically interesting compounds found in basil are linalool (Medeiros Venancio et al 2016), rosmarinic (Kwon et al 2019), oleanolic (OA; Qamar et al 2020) and ursolic acid (UA; Arshad Qamar et al 2010;Kümmritz et al 2014). The latter are triterpenoids, a class of isoprenoid-based secondary metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…Basil and its essential oil are often used in traditional medicine (Irondi et al 2016;Ezeani et al 2017;Bae et al 2020), cosmetics (Vivas Castaño et al 2016;Volpe et al 2018;Yeşil et al 2020), and pharmacology (Sestili et al 2018;Zhan et al 2020). Among the pharmacologically interesting compounds found in basil are linalool (Medeiros Venancio et al 2016), rosmarinic (Kwon et al 2019), oleanolic (OA; Qamar et al 2020) and ursolic acid (UA; Arshad Qamar et al 2010;Kümmritz et al 2014). The latter are triterpenoids, a class of isoprenoid-based secondary metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…Terpenes represent one such class of compounds in cannabis that until recently have not been thoroughly investigated for potential therapeutic effects (Russo, 2011). While a growing body of literature suggests that terpenes might offer beneficial effects ranging from antinociception (Peana et al ., 2006; Batista et al ., 2008, 2010; Gertsch et al ., 2008; Berliocchi et al ., 2009; Kuwahata et al ., 2013; Nascimento et al ., 2014; Piccinelli et al ., 2015, 2017; Medeiros Venancio et al ., 2016; Araujo-Filho et al ., 2017; Segat et al ., 2017; Aguilar-Avila et al ., 2019; Aly et al ., 2019; Abbasijahromi et al ., 2020; LaVigne et al ., 2021; Bilbrey et al ., 2022), to anxiolytic properties (Linck et al ., 2010; Souto-Maior et al ., 2011; Bahi et al ., 2014; Harada et al ., 2018; Abbasijahromi et al ., 2020), the pharmacological mechanisms of these purported effects remain poorly characterized (see Russo, 2011 for a summary of the proposed pharmacological effects of terpenes). Two recent reports suggested that CB1 receptors might be one target for a number of terpenes present in cannabis (LaVigne et al ., 2021; Bilbrey et al ., 2022) as evidenced by cannabimimetic activity in the tetrad assay.…”
Section: Discussionmentioning
confidence: 99%
“…1 In the past few years, the majority of research in this field has focused on novel approaches for delivering drugs, depending on the drug-delivery system. 2,3 Cancer is defined as a disorder in which extraordinary cells are amplified by escaping the traditional regulations of cellular division. Ovarian cancer SKOV-3 cells are a primary type of cancer cells.…”
Section: Introductionmentioning
confidence: 99%